A Climatological Study of Hurricane Force Extratropical Cyclones - Laiyemo, Razaak (2012)
Using data compiled by the National Weather Service Ocean Prediction Center, a hurricane force extratropical cyclone climatology is created for three cold seasons. Using the criteria of Sanders and Gyakum (1980), it is found that 75% of the 259 storms explosively deepened. The frequency maximum in the Atlantic basin is located to the southeast of Greenland. In the Pacific, two maxima to the east of Japan are identified. These results are in good agreement with previous studies, despite different cyclone subgroups, datasets, and methodologies. Composite analyses illustrate the hurricane force wind subgroup of extratropical cyclones, similar to other extratropical cyclones, form in regions of anomalously strong baroclinicity and begin to intensify upstream of an upper-level positive PV anomaly. By the end of the 24-hour period of maximum deepening rate, the composite storm structure appears nearly vertically stacked. Shortly after this time, the storm begins to weaken. There is some indication that diabatic processes serve as an additional energy source. Brief examination of predictability using ECMWF and NCEP ensemble data to analyze two randomly-selected storms indicate significant features like storm track and intensity are not properly captured by the ensemble prediction systems. The original document contains color images.